2017
DOI: 10.1016/j.gaitpost.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Continuous use of textured insole improve plantar sensation and stride length of people with Parkinson’s disease: A pilot study

Abstract: Findings involving the acute benefits of textured insoles on gait in people with Parkinson's disease (PD) are still controversial. To our best acknowledge, the continuous use of textured insoles on gait in people with PD has not been investigated yet. The aim of this pilot study was to obtain preliminary data of the effects of textured insoles on gait and plantar sensation in people with PD after one-week intervention and one-week follow-up period. Nineteen patients with PD were distributed into two groups: ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 13 publications
0
37
1
Order By: Relevance
“…It has been previously reported that individuals with PD have signs of sensory impairment, both peripherally and centrally, and sensory processing deficits contribute to movement disorders in subjects with PD [11,32,33]. Based on these findings, different methods of plantar sensory stimulation have been investigated to improve movement alterations in PD, with promising results for clinical applications [14,[34][35][36]. The Pagnussat and coworkers procedure used a stimulation based on the application of a pressure via rounded tips in the four target areas of the feet (two in each foot, corresponding to the head of the big toe and the base of the first metatarsal bone).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that individuals with PD have signs of sensory impairment, both peripherally and centrally, and sensory processing deficits contribute to movement disorders in subjects with PD [11,32,33]. Based on these findings, different methods of plantar sensory stimulation have been investigated to improve movement alterations in PD, with promising results for clinical applications [14,[34][35][36]. The Pagnussat and coworkers procedure used a stimulation based on the application of a pressure via rounded tips in the four target areas of the feet (two in each foot, corresponding to the head of the big toe and the base of the first metatarsal bone).…”
Section: Discussionmentioning
confidence: 99%
“…The facilitatory insole produced a significant increase in single-limb support time by normalizing the muscle activation sequence of the tibialis anterior at the time of initial ground contact. Lirani-Silva et al [35] observed benefits offered by textured insoles on plantar sensation and stride length in people with PD after continuous use. A similar improvement in stride length was observed in PD compared to the control group in our study, confirming that plantar stimulation may improve postural instability seen in PD [14,36].…”
Section: Discussionmentioning
confidence: 99%
“…In both studies the results obtained, were compared with the use of a conventional slab and those obtained with the use of a custom-made foot-insole facilitator; the data suggest that the use of a facilitating insole can be considered a low-cost and effective treatment strategy for optimizing the postural responses and gait of the patient suffering from Parkinson disease, providing evidence on the role that the somatosensory system plays in the instauration of the postural instability of patient which, however, has not been observed in Parkinsonism. Similarly, Lirani-Silva E. et al [21], observed in their pilot study how the continuous use of textured insoles for one week bene its plantar sensation and gait in patients with PD. Their results underlinded the hypothesis that enhanced somatosensory feedback to the sensory system result in an improved motor output of gait in patients affected by PD.…”
Section: Introductionmentioning
confidence: 83%
“…"dual-task performance" [17][18][19][20]. Alterations in the sensor-motor control of these functions appear to be irrefutable at present with studies that over the years have wanted to highlight the fundamental role that in this context may have orthostatic and orthodynamic plantigrade support of a Parkinsonian patient [16,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The studies using insoles to stimulate plantar foot used a static protocol of stimulation prior to analysis of the gait [54,56]; or used textured insole [57][58][59]. A variety of stimulation periods were found with the other procedures, ranging from a few seconds [54], minutes [56], and even days [59]. As regards the anatomical location of mechanical stimulation on plantar foot, most studies stimulated the head of the big toe and the base of the first metatarsal bone.…”
Section: Protocols Of Plantar Foot Stimulation and Sites Of Stimulationmentioning
confidence: 99%